Thompson & Thompson genetics in medicine - Nussbaum, Robert L.; McInnes, Roderick R.; Willard, Huntington F.; Thompson, James S. (Saunders/Elsevier, 2007)
Through six editions, Thompson & Thompson’s Genetics in Medicine has been a well-established favourite textbook on this fascinating and rapidly evolving field, integrating the classic principles of human genetics with modern molecular genetics and the latest clinical applications. Clearly written and abundantly illustrated, the New 7th Edition retains all of the features that have made its predecessors so popular while also comprehensively detailing all of the new developments and advances in the field.--Provided by publisher.